Utilização das tecnologias de informação no contexto das cidades inteligentes em grandes cidades : o caso de Lisboa - Aires, Joana Marta Ferreira (2016)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence